GOVERNMENT INTERVENTION IN DETERMINING PRICES ACCORDING TO IBN TAIMIYAH’S - Khanifah Nurfaizah (Universitas Airlangga, 2019)
Government intervention in pricing, has always been debated among economists. Islam as a religion which the last has a good economic outlook in terms of micro, macro as well as domestic scale, regional and even international. Prophet was the first in Taimiyah’s book by the public regarding the intervention price, at the time of the Prophet give answers like the following hadith